2022
DOI: 10.3847/psj/ac7de7
|View full text |Cite
|
Sign up to set email alerts
|

Heliocentric Effects of the DART Mission on the (65803) Didymos Binary Asteroid System

Abstract: The Double Asteroid Redirect Test (DART) is NASA’s first kinetic impact–based asteroid deflection mission. The DART spacecraft will act as a projectile during a hypervelocity impact on Dimorphos, the secondary asteroid in the (65803) Didymos binary system, and alter its mutual orbital period. The initial momentum transfer between the DART spacecraft and Dimorphos is enhanced by the ejecta flung off the surface of Dimorphos. This exchange is characterized within the system by the momentum enhancement parameter,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The ejecta particles that remain in the system or get redeposited on either asteroid do not contribute to the heliocentric changes of the system. Makadia et al (2022) concluded that the changes to the heliocentric orbit of Didymos imparted by DART are indeed minor and cannot send the Didymos system on a collision course with Earth after the DART impact.…”
Section: Didymos System Heliocentric Orbit Changesmentioning
confidence: 99%
“…The ejecta particles that remain in the system or get redeposited on either asteroid do not contribute to the heliocentric changes of the system. Makadia et al (2022) concluded that the changes to the heliocentric orbit of Didymos imparted by DART are indeed minor and cannot send the Didymos system on a collision course with Earth after the DART impact.…”
Section: Didymos System Heliocentric Orbit Changesmentioning
confidence: 99%
“…In the case of a binary system, there are two β values to be considered: a β value for Dimorphos, which has been the focus of DARTʼs investigation (Cheng et al 2023), and a heliocentric β value for the Didymos system, the momentum enhancement factor caused by the ejecta that escapes the binary system. A pre-impact analysis examined the range of possible heliocentric β values that could result from DARTʼs impact and demonstrated that the Didymos system would not be shifted onto a collision course with the Earth (Makadia et al 2022), although, a measure of the Didymos systemʼs deflection about the Sun potentially could be made in the future (Richardson et al 2022). A measurement of heliocentric β for the Didymos system has not yet been made; though, multiple high-quality stellar occultation observations obtained in 2022-2023, including detections of Dimorphos as the smallest object ever observed during an occultation campaign, may make such a measurement possible in the next few years (Makadia et al 2024).…”
Section: The Binary Didymos Systemmentioning
confidence: 99%
“…Pre-impact studies were important in establishing the methodologies to be applied to investigate the post-impact dynamics of the Didymos system and in considering a wide range of possible outcomes (Agrusa et al 2020(Agrusa et al , 2021Meyer et al 2021Meyer et al , 2023bAgrusa et al 2022;Makadia et al 2022;Richardson et al 2022). Overall, the DART kinetic impact test resulted in a small change to the dynamical state of the Didymos system that is generally consistent with pre-impact expectations, with the biggest surprises attributed to the flattened shape of Didymos compared to the radar-based model and the oblate pre-impact shape of Dimorphos (Richardson et al 2024).…”
Section: The Binary Didymos Systemmentioning
confidence: 99%
“…If both bodies have similar mechanical properties, ejecta binding to the system is a function of the bodies' locations in the system's gravity well. The escape speed for ejecta from the system can be approximated by summing the effects of gravity from both bodies at the surface of the target (Makadia et al 2022). A simple analysis shows that the secondary is the better target when the ratio of secondary to primary radii is greater than the corresponding ratio of masses.…”
Section: Deflecting a Binary Asteroidmentioning
confidence: 99%